2022
DOI: 10.14507/epaa.30.5955
|View full text |Cite
|
Sign up to set email alerts
|

Examining racial discourse in equity reports: Florida’s public Hispanic serving institutions

Abstract: Public Hispanic serving institutions (HSIs) play a prominent role in educating racially minoritized students, thus making them valuable sites for examining higher education increased attention to state and institution-level diversity policy and plans. Institutional diversity, equity, and inclusion (DEI) plans, serve as public statements regarding institutional priorities, illuminate how racial equity is centered or decentered. This research engages 10 Equity Reports at public two-year and four-year HSIs in Flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…It is motivated by the following question: How do discourses that surround CRT bans reveal and speak to racialized emotions? The research underscores the racialized dynamics of education policy (Gillborn, 2005(Gillborn, , 2014Guinier, 2004;Vue, 2021a), highlighting discourse as a key site in the production of racial meaning and politics (Arellano & Vue, 2019;Briscoe & Khalifa, 2015;Casellas, 2022;Iverson, 2005;Moses et al, 2019;Paguyo & Moses, 2011). The salience of emotions in the actual language of anti-CRT legislation points toward the need to understand its role in the political dynamics that surround education policy, especially those concerning race in education.…”
Section: -Aristotlementioning
confidence: 93%
See 2 more Smart Citations
“…It is motivated by the following question: How do discourses that surround CRT bans reveal and speak to racialized emotions? The research underscores the racialized dynamics of education policy (Gillborn, 2005(Gillborn, , 2014Guinier, 2004;Vue, 2021a), highlighting discourse as a key site in the production of racial meaning and politics (Arellano & Vue, 2019;Briscoe & Khalifa, 2015;Casellas, 2022;Iverson, 2005;Moses et al, 2019;Paguyo & Moses, 2011). The salience of emotions in the actual language of anti-CRT legislation points toward the need to understand its role in the political dynamics that surround education policy, especially those concerning race in education.…”
Section: -Aristotlementioning
confidence: 93%
“…CRDA enables a micro-level examination of discourse in its various forms (e.g., text, verbal speech, semiotics) to understand how it reifies, adapts, or counteracts hegemonic ideologies. Studies that have examined institutional discourses show how policy documents, such as diversity agendas and equity reports, engender racialized meanings with implications for educational equity (Casellas, 2022; Iverson, 2005). Other research has demonstrated the continuing need to explore the multiple competing discourses while interrogating issues of access to the processes that shape discourses about race, diversity, and equity (Arellano & Vue, 2019; Briscoe & Khalifa, 2015; Dumas, 2013; Freidus, 2022; Hernández, 2022; Moses et al, 2019; Paguyo & Moses, 2011; Vue, 2021a; Vue et al, 2017).…”
Section: Methodology: Crdamentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, CDA helps us make transparent the "structural relationships of dominance, discrimination, and control as manifested in language" (Wodak, 1995, p. 204) used in policy texts. This kind of discursive analysis has been used to examine state-level reforms related to admissions (Winkle- Wagner et al, 2014), diversity initiatives (Casellas Connors, 2022), college completion (Mansfield & Thachik, 2016), community college equity (Ching et al, 2020;. Through this discursive method, we collected publicly available state-level attainment documents to better understand the underlying discourse related to improving attainment broadly and specifically for the Latinx community.…”
Section: Methodsmentioning
confidence: 99%
“…Having grown in prominence over the past several decades, diversity plans operate as a tool for DEI organizational change. However, the examination of diversity plans at land-grant institutions and community colleges, has shown how they advance color evasive language, present a deficit framework around students, and include a significant level of heterogeneity (Casellas Connors, 2021, 2022; Ching et al, 2018; Felix et al, 2018; Iverson, 2007). Specific to land-grant universities, Iverson (2005, 2007) highlights how diversity plans were not neutral, but position students of color as outsiders, disadvantaged, and at-risk and perpetuate exclusionary campus practices that reinforce inequality.…”
Section: Situating Institutional Discoursementioning
confidence: 99%